Notes of Honey Buzzard and Other Birds in Dumai and Rupat Island, Riau Province, Indonesia - Sukmantoro, Wishnu; Cye, Lim Kim; Tiah, Lim Au; Iqbal, Mohammad; Ng, Francis (Universitas Atma Jaya Yogyakarta, 2006)
Dumai are a town that located coastal area in the Nothern part of Pekan Baru, a capital city of Riau Province (1o 41â€™ 04.1â€ N, 101o 26â€™ 14,1â€ E). Dumai is margined directly by Rupat Island and Bengkalis Island in the North and Duri District in the South and East. On February 17, survey is conducted in Dumai harbour which vegetation are dominated rural plant and small scale mangrove. Only few records of bird are reported on 1980 such as storm stork Ciconia stormi (Holmes 1980).